On the Added Modal Coefficients of a Rotating Submerged Cylinder Induced by a Whirling Motion—Part 1: Experimental Investigation - Rafel Roig; Xavier Sánchez-Botello; Esteve Jou; Xavier Escaler (Journal of Marine Science and Engineering, 2023)
The operation of submerged rotating machines, such as marine current or tidal turbines, can present deleterious fluid phenomena that may provoke extreme structural vibrations. To predict their dynamic responses, it is necessary to know the added modal coefficients of their runners under a whirling motion. For that purpose, a bespoke test rig was designed to investigate the added modal coefficients of a submerged cylinder, which could rotate at different speeds both in air and completely submerged in water inside a cylindrical tank. First, the modes of vibration were experimentally measured by exciting the cylinder with a push-release method during steady tests or with ramps in rotating speed during transient tests. The calculated natural frequencies and damping ratios were then used in a mathematical model of the dynamic system to calculate the added modal coefficients. During steady tests, the natural frequencies and damping ratios of the whirling modes changed significantly as a function of the rotating speed. Additionally, a whirling mode was observed to change its direction at a given rotating speed. During transient tests, rotating speed ramps with high accelerations were found to present lower lock-in amplitude and frequencies. Moreover, fast downward ramps presented lock-in amplitudes four times higher than fast upward ramps. Consequently, the added modal coefficients changed accordingly as a function of the rotating speed, ramp acceleration, and ramp direction. For these reasons, it was confirmed that the modal responses of submerged rotating bodies must be calculated for each operational rotating speed, even at low velocities, and for each transient event in order to precisely predict their vibration behaviors.